Coercion in the marriage contract - The coercive marriage - Lecturer - Hussein Alwan, Dr. Zina (The college of law and political science journal, 2023)
his in voucher s’man a her made and woman the preserved has Bari-Al his to according duties his all it on and ,rights of money his has which ,life and ,place her has woman the so ,Almighty The by broken is which ,composition does who someone with her marry to right her override to permissible not is it of influence the under marriage considered legislator Iraqi the and ,her suit not.in